Analisis Sinamot Sebagai Simbol Stratifikasi Sosial Masyarakat Batak Toba di Desa Amborgang Kecamatan Siempat Nempu Kabupaten Dairi - Desnia Silaban; Martua Sihaloho; Jupalman W Simbolon; Maringan Sinambela; Harisan Boni Firmando (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This research aims to discuss sinamot in the Toba Batak tradition and find out that sinamot is a social stratification of the Toba Batak traditional community in Amborgang Village, Siempat Nempu sub-district, Dairi Regency. Method The research used is qualitative research with a descriptive approach. The author uses data collection techniques include observation, interviews and documentation. Based on research that has been carried out, the author obtained the results that the meaning of sinamot in the Toba Batak ethnic group is marriage payments in the form of money and wealth given by the paranak (male) to the parboru. (Woman). Furthermore, based on research, the function of ancient sinamot among the Toba Batak ethnic group was to Guarantees women’s rights in the form of property given as capital for the bride and groom when they marry, while the function of sinamot today in the Toba Batak ethnic group is a means of payment used to finance traditional wedding parties. Changes in the function of sinamot in the past in the Toba Batak ethnic group have changed, seen from its form which has changed into money, its function is to finance wedding parties and the process of giving sinamot is determined based on the considerations of both families. Future bride and groom. The conclusion shows that the form of sinamot evolved from valuable possessions changed Form into money. The determination of the number of sinamot is carried out at the stage of the marhata sinamot traditional event. As time goes by, the tradition of giving sinamot to the Toba Batak ethnic group in ancient times has changed its function in the present day so that sinamot is no longer aimed at women but is given to the woman’s parents through a negotiation process between the two familie.